Measure of tolerance level in rice (Oryza sativa) accessions resistant to white-backed planthopper (Sogatella furcifera) - NALINI, R; GUNATHILAGARAJ, K (The Indian Journal of Agricultural Sciences, 2013)
A laboratory experiment was conducted during 1990 to assess the level of tolerance present in 5 rice accessions (IET 10251’,’IR 58032-1’, ’IR 58036-5’, ’IR 58044-5’ and ’IR 58046-5’) resistant to white-backed planthopper [Sogatella furcifera (Horvath)] compared with susceptible ’TN 1’. Resistant accessions recorded the lowest functional plant-loss index14.27-46.74%), and the loss was only 20% of that in ’TN I’ (78.21 %). Dry weight of insect produced through feeding was maximum in ’TN 1’ (22.13 mg) (4.97-6.83 mg in resistant accessions). Adults that developed on resistant accessions weighed less than those developed on ’TN 1’. The loss in plant biomass for the producion of S.furcifera biomass was less in ’IET 10251’, Thus tolerance contributed to moderate resistance in ’IET 10251’,